PELAKSANAAN PELAYANAN PENDIDIKAN INKLUSI DI SD NEGERI RAWU KOTA SERANG - Pribadi, Reksa Adya; Komariah, Iis; Fariha, Sayidatul; Nazela, Salsa (Autentik : Jurnal Pengembangan Pendidikan Dasar, 2025)
Inclusive education at the elementary school (SD) level is an approach that aims to provide learning opportunities for all students, including those who have special needs. The implementation of inclusive education allows children with special needs to learn together with normal students at school. This research aims to analyze the implementation of inclusive education at SDN Rawu. The research methods used involve class observations, interviews with class teachers and analysis of school policies. To check the validity of the data, researchers used data triangulation techniques. The research results show that there are various strategies and approaches implemented by teachers to support the success of inclusive students. It was found that support from the school, involvement of parents, and teacher training were key factors in optimizing the implementation of inclusive education at SDN Rawu. In implementing inclusive education, the school has provided teachers appropriate to the department and special accompanying teachers who are tough and great at providing services according to the diagnostic needs of children with special needs. Obstacles such as a lack of resources and a curriculum that is not always supportive need to be a common concern to increase the effectiveness of inclusion at the primary education level. This research provides valuable insights for the development of inclusive education policies and practices at the elementary school level.